2022
DOI: 10.1097/pcc.0000000000002973
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Decision Support in the PICU: Implications for Design and Evaluation*

Abstract: To assess the current landscape of clinical decision support (CDS) tools in PICUs in order to identify priority areas of focus in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…When a clinical problem is insufficiently defined or the research priorities have not been fully considered and debated, scoping reviews and consensus conferences can aid in lending clarity to what is known and what future research priorities should be. In the last 3 years, PALISI has focused on aspects of hemopoietic stem-cell transplantation (HCT) (16)(17)(18), transfusion and bleeding (19,20), measuring outcomes (21)(22)(23), and clinical decision support (24). Table 2 shows other examples of consensus conferences and their links to prior or future PALISI Network studies.…”
Section: Scoping Reviews and Consensus Meetingsmentioning
confidence: 99%
“…When a clinical problem is insufficiently defined or the research priorities have not been fully considered and debated, scoping reviews and consensus conferences can aid in lending clarity to what is known and what future research priorities should be. In the last 3 years, PALISI has focused on aspects of hemopoietic stem-cell transplantation (HCT) (16)(17)(18), transfusion and bleeding (19,20), measuring outcomes (21)(22)(23), and clinical decision support (24). Table 2 shows other examples of consensus conferences and their links to prior or future PALISI Network studies.…”
Section: Scoping Reviews and Consensus Meetingsmentioning
confidence: 99%
“…These limitations were highlighted in a recent study in which most pediatric critical care providers were neutral or disagreed that current predictive algorithms provided useful information. 96 Providers agreed that important goals included evidence-based CDSS with a proven impact on patient safety, that were well-placed and delivered at the right time. 96 Providers expressed concern about the accuracy of CDSS, the effect on practitioners' critical reasoning, and the burden of increased time spent on the computer.…”
Section: Clinical Decision Supportmentioning
confidence: 99%
“…96 Providers agreed that important goals included evidence-based CDSS with a proven impact on patient safety, that were well-placed and delivered at the right time. 96 Providers expressed concern about the accuracy of CDSS, the effect on practitioners' critical reasoning, and the burden of increased time spent on the computer. 96…”
Section: Clinical Decision Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these barriers may include alert fatigue, inappropriate alerting, disrupted workflows, and perceived threats to autonomy. 2,4 In a survey of 45 institutions, Dziorny et al 5 found that pediatric intensive care practitioners viewed CDS tools as intrusive with concerns for diminished critical thinking. Williams et al 3 acknowledge these barriers as a potential explanation for the modest impact on improving their outcome of interest.…”
mentioning
confidence: 99%